Bronchopulmonary and vascular anomalies are frequent in children with oesophageal atresia. (11th December 2019) - Lejeune, Stephanie; Le Mee, Armelle; Petyt, Laurent; Hutt, Antoine; Sfeir, Rony; Michaud, Laurent; Fayoux, Pierre; Deschildre, Antoine; Gottrand, Frederic; Thumerelle, Caroline
Abstract: Aim: Oesophageal atresia is frequently associated with other malformations, and our aim was to use computed tomography (CT) to explore intrathoracic malformations in patients with this condition. Method: This was retrospective study of children aged 0‐16 with oesophageal atresia who were born in 1996‐2013 and followed up at the French reference centre for rare oesophageal diseases at the University of Lille. Computed tomography scans were available for 48 of the 234 patients during follow‐up visits, and these were reviewed by a thoracic radiologist. Results: More than two‐thirds of the scans were performed to explore persistent respiratory symptoms. We found that six patients had a pulmonary malformations: four lobar agenesis, one right pulmonary aplasia and one congenital cystic adenomatoid malformation. Computed tomography enabled us to diagnose unexpected thoracic malformations in 16 patients: four lobar agenesis, six arteria lusoria, five persistent left superior vena cava and one partial anomalous pulmonary venous return. It also confirmed the diagnoses of suspected malformations in five patients: one congenital cystic adenomatoid malformation, one pulmonary hypoplasia, two right‐sided aortic arches and one communicating bronchopulmonary foregut malformation. Conclusion: Intrathoracic anomalies were frequently associated with oesophageal atresia, and contrast‐enhanced chest CT scans should be performed on patients with persistent respiratory symptoms.